Psikologi Perkembangan Anak bagi Pengembangan Sosial Emosional Anak Usia Dini - Sukatin, Sukatin (Institut Agama Islam Sunan Giri Ponorogo, 2021)
Early childhood education, which is the foundation for education, should be done holistically. It is hoped that all aspects of development in children are optimally stimulated. Emotional intelligence is responsible for self-esteem, self-awareness, social sensitivity and social adaptability. If you have high emotional sensitivity, you will be able to understand the various feelings that arise and be able to recognize yourself. Emotional intelligence is a form of ability possessed by a person so that he can know himself and others and can put himself in other people's situations and the environment proportionally. The research method used in this research is Library Research. The data used are sourced from scientific journals, scientific books, newspapers, internet, or other written and electronic sources. The data analysis technique used is descriptive analytical